2018
DOI: 10.3389/fchem.2018.00039
|View full text |Cite
|
Sign up to set email alerts
|

Separation, Identification, and Bioactivities of the Main Gallotannins of Red Sword Bean (Canavalia gladiata) Coats

Abstract: The red sword bean (Canavalia gladiata) is an underutilized edible bean cultivated in China. It was previously found to have the highest content of antioxidant polyphenols among 42 edible beans, mainly gallic acid, and gallotannins in its red bean coat, an apparently unique characteristic among edible beans. In this study, the main phenolic compounds in red sword bean coats were further separated by Sephadex LH-20 column chromatography, and identified by LC-MS/MS. Furthermore, the FRAP and ABTS antioxidant act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 31 publications
(72 reference statements)
1
11
0
Order By: Relevance
“…The HHDP moiety arises due to the oxidative C-C bond formation between neighboring galloyl residues within the ellagitannin structure. Another group of hydrolyzable tannins is represented by gallotannins (polygalloyl esters of glucose or other polyol carbohydrate), which have a simpler structure and more restricted distribution in nature than ellagitannins [160,161]. A molecular precursor of both gallotannins and ellagitannins in plants is gallic acid (3,4,5-trihydroxybenzoic acid), and the initial stages of biosynthesis are common to both of these groups of phytochemicals [158].…”
Section: Chemical Properties and Natural Sources Of Eamentioning
confidence: 99%
“…The HHDP moiety arises due to the oxidative C-C bond formation between neighboring galloyl residues within the ellagitannin structure. Another group of hydrolyzable tannins is represented by gallotannins (polygalloyl esters of glucose or other polyol carbohydrate), which have a simpler structure and more restricted distribution in nature than ellagitannins [160,161]. A molecular precursor of both gallotannins and ellagitannins in plants is gallic acid (3,4,5-trihydroxybenzoic acid), and the initial stages of biosynthesis are common to both of these groups of phytochemicals [158].…”
Section: Chemical Properties and Natural Sources Of Eamentioning
confidence: 99%
“…Reports indicated that sword bean originated from the Asian continent and is now known in the tropics as an introduced species. The red sword bean is one of the edible beans of China reportedly rich in antioxidant polyphenols with great medicinal uses [41,42]. Furthermore, the seed coat of the bean is rich in gallic acid and its derivatives, mainly gallotannins, a common trait found in legume polyphenols [41].…”
Section: Sword Bean (Canavalia Gladiata L)mentioning
confidence: 99%
“…The red sword bean is one of the edible beans of China reportedly rich in antioxidant polyphenols with great medicinal uses [41,42]. Furthermore, the seed coat of the bean is rich in gallic acid and its derivatives, mainly gallotannins, a common trait found in legume polyphenols [41]. The chemical composition of seeds of sword bean has been reported and compares quite well with soybean [43][44][45].…”
Section: Sword Bean (Canavalia Gladiata L)mentioning
confidence: 99%
“…Tannins in ripened seeds and ripened split beans of C. cathartica and C. maritima decreased substantially on cooking [24,44]. Gallotannins have been extracted from red bean coat of C. gladiata which showed potent antioxidant as well as antibacterial activity [46].…”
Section: Phenolicsmentioning
confidence: 99%